Efektivitas Kelompok Usaha Bersama (KUBE) di Desa Banglas Kecamatan Tebing Tinggi Kabupaten Kepulauan Meranti - silvia; Sujianto Sujianto (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2021)
Poverty is a socio-economic condition of citizens who are unable to meet basic needs appropriate to humanity. One of the government-implemented models for empowerment of the poor is the existence of KUBE. A joint business group (KUBE) is a collection of families of the poor that are formed, grow and develop on their own initiative, associate with each other and live in certain regional units. With the help of KUBE, it is hoped that the KUBE that is being managed will continue to grow and bring about changes in the social well-being of members of the Joint Business Group (KUBE). In this article, the author uses a qualitative research method with a descriptive approach. The researcher uses Sharma's theory of organizational effectiveness. The results of this study showed that the effectiveness of the Joint Business Group (KUBE) in Banglas Village, Tebing Tinggi District, Meranti Islands Regency was still less effective and not optimal in implementation because there were still inhibiting factors, namely conflict among members causing KUBE management to malfunction, lack of skills, Human Resources (HR) and unfair competition.